Solubilisasi Fosfat Anorganik oleh Burkholderia spp. pada Rizosfer Kelapa Sawit (Elaeis guineensis Jacq.) di Tanah Mineral Masam - Gregorius Baskara Aji Nugraha; Ruli Wandri; Dwi Asmono (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Nugraha et al, 2019.Â Solubilization of Inorganic Phospate by Burkholderia spp. Associated with Oil Palm Rhizosphere in Mineral Acid Soil. JSLO 8(1):86-93.Phosphate Solubilizing Bacteria (PSB) play important role by enhancing phosphate availability bounded with Al3+ orÂ  Fe3+ in acidic soils to oil palm plants through release the inorganic phosphate by enzyme or organic acids solubilization. The aims of this study were to isolate of PSB from oil palm rhizosphere and to conduct a comparative analysis of the solubility inorganic phosphates source by selected PSB. The ability of 15 selected PSB to grow and solubilize aluminum phosphate (AlPO4) and iron phosphate (FePO4) was examined and identified. The highest phospate solubilising efficiency showed K3.1 isolate with phosphate solubilization index 3.2 on NBRIP media. Quantitative analysis revealed that isolate K3.1 solubilized 53.52 mg/mL phosphate in 5 days after being inoculated in AlPO4 containing liquid medium, isolate A4 solubilized 63.45 mg/mL phosphate in 5 days after being inoculated in FePO4 containing liquid medium accompanied by a decrease in pH of the growth medium. Based on the 16s rRNA gene sequence analysis, isolate K3.1 and A.4 were closely related to Burkholderia arboris and Burkholderia gladioli. This potential isolates can be used in order to make oil palm crops more sustainable especially on marginal soil with low pH and less dependent on inorganic P fertilizers.Â